2011
DOI: 10.1584/jpestics.g10-84
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of alkyl gallates and related compounds against Ralstonia solanacearum

Abstract: Antibacterial activity of alkyl gallates and their analogs against Ralstonia solanacearum was examined. Methyl gallate showed the strongest activity among the alkyl gallates; activity decreased as the carbon number of esters increased. This tendency of alkyl gallates to act against R. solanacearum was dissimilar to its previously reported action against Gram-negative and Gram-positive bacteria and fungi. Among related compounds with a differing position and number of phenolic hydroxyl groups, methyl 2,3-dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Methyl gallate (compound 2 ) was much more active than gallic acid (compound 1 ). The measurements of antibacterial activity in our study agreed with those of previous reports [ 4 , 37 , 38 ]. Compounds with similar structures, such as 3 and 4 , and 5 and 6 , had similar antibacterial activity and spectra ( Table 1 ).…”
Section: Resultssupporting
confidence: 93%
“…Methyl gallate (compound 2 ) was much more active than gallic acid (compound 1 ). The measurements of antibacterial activity in our study agreed with those of previous reports [ 4 , 37 , 38 ]. Compounds with similar structures, such as 3 and 4 , and 5 and 6 , had similar antibacterial activity and spectra ( Table 1 ).…”
Section: Resultssupporting
confidence: 93%
“…Methyl 4-hydroxycinnamate and methyl 4-hydroxybenzoate (methyl paraben) were also tested based on antibacterial activity against R. solanacearum shown in our previous experiments …”
Section: Resultsmentioning
confidence: 99%
“…We also reported that hydroxycinnamic acids and alkyl gallates showed anti-R. solanacearum activity . Subsequent studies clarified that phenylpropanoids and their degrading metabolites, including HAAs, are involved in the interaction between tomato and R.…”
Section: Discussionmentioning
confidence: 99%
“…The compound geraniin was also shown to have antibacterial activity. This geraniin effect was reported against Escherichia coli , Staphylococcus aureus (Adesina et al 2000 ; Gohar et al 2003 ), Helicobacter pylori (Funatogawa et al 2004 ), Pseudomonas aeruginosa (Adesina et al 2000 ), Pseudomonas cichorii (Delisle-Houde et al 2020 ), Pseudomonas fluorescens (Kurihara et al 1993 ), Ralstonia solanacearum (Ooshiro et al 2011 ), Streptomyces scabies (Ushiki et al 1998 ), and Xanthomonas campestris pv. vitians (Delisle-Houde et al 2020 ).…”
Section: Introductionmentioning
confidence: 90%